2011
DOI: 10.1542/peds.2011-0742
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing Rate of Biliary Atresia in Taiwan: A Survey, 2004–2009

Abstract: A significant decrease in BA incidence in Taiwan since 2007 has been noted and may be related to improvements in the general socioeconomic status and the popularity of rotavirus vaccination. Although more evidence is needed to establish a direct correlation, this phenomenon may shed light on possible causes of and preventive interventions for BA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 30 publications
2
37
1
Order By: Relevance
“…In our study, the number of new BA cases tends to increase every year because of an improved diagnostic algorithm (using an abdominal ultrasound and stool color card). The incidence of BA in 2013 was similar to the number reported in Taiwan . As CH2 is the single pediatric LT center in Southern Vietnam, patients from the Mekong River Delta, Central Coast, Central Highlands, and the Southeast Region are transferred to this center to follow up their chronic liver disease, also leading to the increase of new BA cases.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In our study, the number of new BA cases tends to increase every year because of an improved diagnostic algorithm (using an abdominal ultrasound and stool color card). The incidence of BA in 2013 was similar to the number reported in Taiwan . As CH2 is the single pediatric LT center in Southern Vietnam, patients from the Mekong River Delta, Central Coast, Central Highlands, and the Southeast Region are transferred to this center to follow up their chronic liver disease, also leading to the increase of new BA cases.…”
Section: Discussionsupporting
confidence: 57%
“…BA occurs in 0.25/10 000 live births in Europe , in 0.8/10 000 in New York City , and some studies report a higher prevalence in Asian countries . In a study performed in Taiwan, the incidence of BA was 0.8/10 000 live births from mothers from Southeast Asia, including Vietnam .…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of BA in the USA is about 0.73 per 10 000 live births with a slight female predominance . The incidence is lower in some European countries such as France (0.51 per 10 000) but higher in Asia, as in Taiwan (1.23 per 10 000) . Left untreated, BA is fatal; the only effective treatments are hepatic portoenterostomy (Kasai operation) and liver transplantation .…”
Section: Biliary Atresiamentioning
confidence: 99%
“…37 The incidence is lower in some European countries such as France (0.51 per 10 000) but higher in Asia, as in Taiwan (1.23 per 10 000). 38,39 Left untreated, BA is fatal; the only effective treatments are hepatic portoenterostomy (Kasai operation) and liver transplantation. 40 In children, BA is the most common cause of end-stage liver disease and the leading indication for liver transplantation.…”
Section: Biliary Atresiamentioning
confidence: 99%
“…By comparison, Bobo et al[19] did not detect rotavirus (groups A, B or C) RNA from infant BA liver specimens or controls. A more recent study by Lin et al[20] found a significant decrease in the incidence of BA in Taiwan following introduction of a rotavirus vaccination. The authors proposed that although rotavirus vaccination is initiated at 2 months of age, later than the usual age of onset of BA, herd immunity might have decreases rotavirus infection during pregnancy or the neonatal period.…”
Section: Perinatal Virus Infection and Biliary Atresiamentioning
confidence: 99%